The Personality of the Main Character in the Novel “The Rebellious Spirits” by Gibran Khalil Gibran (A Psychological Analytical Study) - Rizki Gunawan; Mohammad Zainal Hamdy; Uswatun Hasanah (Al-Irfan : Journal of Arabic Literature and Islamic Studies, 2021)
Personality is very influential on individual behavior, especially in social matters and in solving life's problems. Every individual has a different personality. The personality of each individual can be influenced by the sharing of factors that give rise to social phenomena in interacting with others every day. This research is a qualitative descriptive study with a type of librariy research. The data collection technique uses documentation techniques which are included in the technique or reading and recording. This type of research. The data collection’s technique is done by reading, translation, and taking. The data analysis technique is that using. The results of this study are: 1) who personalitiy’s structure of the main character in Al- Arwah Al- Mutamarridah. 2) what cause of personality’s type in Al- Arwah Al- Mutamarridah.